Evaluation of a new method of calculating breast tumor volume based on automated breast ultrasound - Ma, Jing-Jing; Meng, Shan; Dang, Sha-Jie; Wang, Jia-Zhong; Yuan, Quan; Yang, Qi; Song, Can-Xu (Frontiers in Oncology, 2022)
Objective: To evaluate the effectiveness and advantages of a new method for calculating breast tumor volume based on an automated breast ultrasound system (ABUS). Methods: A total of 42 patients (18–70 years old) with breast lesions were selected for this study. The Ivenia ABUS 2.0 (General Electric Company, USA) was used, with a probe frequency of 6–15 MHz. Adobe Photoshop CS6 software was used to calculate the pixel ratio of each ABUS image, and to draw an outline of the tumor cross-section. The resulting area (in pixels) was multiplied by the pixel ratio to yield the area of the tumor cross-section. The Wilcoxon signed rank test and Bland-Altman plot were used to compare mean differences and mean values, respectively, between the two methods. Results: There was no significant difference between the tumor volumes calculated by pixel method as compared to the traditional method (P＞0.05). Repeated measurements of the same tumor volume were more consistent with the pixel method. Conclusion: The new pixel method is feasible for measuring breast tumor volume and has good validity and measurement stability.